The Law of Teaching Dignified Education - Widiarty, Wiwik Sri; Dinata, Efran (Sahabat Publikasi, 2025)
This study explores the concept and implementation of dignified education in Indonesia, emphasizing the importance of integrating legal, moral, and philosophical values into the national education system. The research is motivated by the increasing cases of academic dishonesty and the weakening of moral values in the academic environment, particularly at the university level. The objective is to analyze how dignified education, rooted in the values enshrined in the 1945 Constitution and National Education Law, can be upheld and safeguarded through legal and philosophical frameworks. Using a normative juridical approach, this literature-based study examines secondary data such as regulations, philosophical theories—especially pragmatism as articulated by John Dewey—and documented cases of educational malpractice. The findings reveal that Indonesia’s legal structure already provides strong support for dignified education, but challenges persist due to the dominance of pragmatic, result-oriented attitudes over idealism in academia. Such attitudes foster unethical practices like the use of assignment jockeys and the commercialization of academic degrees. The study implies that dignified education must go beyond intellectual development to include the nurturing of moral integrity and legal compliance. It calls for a cultural and structural reform in higher education institutions to prioritize integrity and ethical conduct, supported by strict enforcement of academic regulations and promotion of holistic character education. This integration is essential to produce responsible and dignified citizens, which aligns with the national goal of educating the life of the nation.